A predictive study of factors associated with burnout, compassion fatigue, and moral distress among emergency nurses - Salman Amish Alshammari; Chandrakala Sankarapandian; Eddieson Pasay an; Ayed Amesh Alshammary; Analita Gonzales; Jeneth Gutierrez; Maha Sanat Alreshidi; Nojoud Abdullah Alrashidi; Petelyne Pangket; Dolores Cabansag; Sameer Alkubati; Romeo Mostoles; et al. (Scientific Reports)
Abstract Emergency nurses face high demands that potentially lead to burnout, compassion fatigue, and moral distress. This study aimed to identify and assess the predictive factors of burnout, compassion fatigue, and moral distress among Emergency Nurses. A cross-sectional predictive design was employed. Data collected from 290 emergency nurses via Google Forms using convenience sampling from four government hospitals in Hail City, Saudi Arabia. Data collection was conducted between May and June 2024. The findings revealed that socio-demographic factors significantly predict these outcomes, with the regression model explaining 67.9% of the variance. Older age and being female (β = -6.532 for burnout) were consistently associated with lower levels of all three negative outcomes. While nurses with 6–10 years of experience reported lower levels (β = -5.071 for burnout), this benefit didn’t extend to the most experienced group. Shift patterns had a strong impact, with the 3 PM − 11 PM shift being most protective (β = -6.377 for burnout), while the 11 PM − 7 AM night shift correlated with significantly higher distress (β = 3.151 for burnout). Counterintuitively, higher education levels (e.g., Master’s β = 16.437 for burnout) were linked to increased negative outcomes, and the absence of social support (β = -8.726 for burnout) was surprisingly associated with lower levels of these outcomes. Younger nurses, male, and less experienced emergency nurses who are highly educated are more susceptible to burnout, compassion fatigue, and moral distress. These phenomena reveal the need for integrated organizational and educational restructuring, emphasizing the intersection of sociodemographic and occupational characteristics. Strikingly, postgraduate-educated nurses display greater compassion fatigue and moral distress which paradoxically suggests that higher training may subject them to more frequent and heightened ethical dilemmas.